Land records management in India: a plea for reforms - "Faizi, A.A.A. (ed.);Behera, H.C. (ed.)" (New Delhi, 2014)
The edited book has a comprehensive focus on the land records management in India. The book highlights new approaches of land administration and governance mechanisms adopted by various states. The important focus in the book is about modern cadastral survey methodology and also best practices in land administration. This book will be very useful for the revenue officials, surveyors, policy experts and administrators working in the field of land records management. The readers will be benefited immensely from the contributions of selected erudite scholars and champions of land record management in India. The book will also be useful for the students and researchers working in the field of land management, land governance, cadastral survey, modern cadastral survey, etc. from across disciplines. The book will be useful for State government and Central Government to understand the practicality of land issues.
Keywords: Land titles-Registration and transfer-Technological inno